A meeting place: Translating Ben Wright's Passing Strange and Wonderful to the screen. Issue 1 (1st July 2013) - Zanotti, Marisa
This article is an idea for screen collaboration that places at its centre not spectacle but corporeality as well as being a reflection on the process of translation to the screen of UK choreographer Ben Wrights' duet Passing Strange and Wonderful (2007).1 The image that tries to show us how we experience the surface of space through skin, or of the difference between glancing contact and full body impact, is trying to bring the viewer closer to the dancer's experience, not by showing what she sees, but what she senses. The writing explores Brannigan's idea of a corporeal mise-en-scène (2011) and suggests a meeting place for the choreographer and the film-maker where we might begin the process of translation from live to screen by asking what we know about the experience of dancing, of space and of the body and what we might discover through creating images of this knowledge.